Spatially indirect transitions in electric field tunable quantum dot diodes. Issue 3 (10th November 2015) - Rai, Ashish K.; Gordon, Simon; Ludwig, Arne; Wieck, Andreas D.; Zrenner, Artur; Reuter, Dirk
Abstract : We analyse an InAs/GaAs‐based electric field tunable single quantum dot diode with a thin tunnelling barrier between a buried n + ‐back contact and a quantum dot layer. In voltage‐dependent photoluminescence measurements, we observe rich signatures from spatially direct and indirect transitions from the wetting layer and from a single quantum dot. By analysing the Stark effect, we show that the indirect transitions result from a recombination between confined holes in the wetting or quantum dot layer with electrons from the edge of the Fermi sea in the back contact. Using a 17 nm tunnel barrier which provides comparably weak tunnel coupling allowed us to observe clear signatures of direct and corresponding indirect lines for a series of neutral and positively charged quantum dot states.